Impaired fasting glucose prevalence in two nationwide cohorts of obese children and adolescents - Hagman, E (Nature Publishing Group, 2014)
OBJECTIVE: Impaired fasting glucose (IFG), a pre-stage to type 2 diabetes in adults, is also present in obese children. A large variation of the occurrence has been recorded, but the true prevalence is unknown due to lack of larger representative cohort studies. This study was implemented to investigate the prevalence of IFG in two nationwide cohorts of obese children and to find factors that affect the risk of IFG. DESIGN: A cross-sectional study based on data collected from two nationwide registers of obese children in Germany and Sweden, respectively. SUBJECTS: Subjects included were 2–18 years old. 32 907 subjects with fasting glucose were eligible in Germany and 2726 in Sweden. Two cutoff limits for IFG were used: 5.6–6.9 mmol l(−1) according to the American Diabetes Association (ADA) and 6.1–6.9 mmol l(−1)according to the World Health Organization (WHO). Variables collected were gender, age and degree of obesity. Logistic regression was used to calculate odds ratios. RESULTS: The total prevalence of IFG among obese children in the German cohort according to the ADA was 5.7% and according to the WHO it was 1.1%. In Sweden, the corresponding prevalence was 17.1% and 3.9%, respectively. IFG risk was correlated with increasing age, male sex and degree of obesity. CONCLUSIONS: IFG is highly prevalent among obese children. Age and degree of obesity are positively correlated with the risk of having IFG. There are large regional differences. After adjustments, obese children in Sweden, due to unknown reasons, have a 3.4- to 3.7-fold higher risk of having IFG than obese children in Germany.